IoT and transparent solar cell based automated green house monitoring system for tomato plant cultivation - Yus Rama Denny; Endi Permata; Adhitya Trenggono; Vaka Gustiono (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
This study aimed to develop and test the feasibility of a smart greenhouse prototype media that is used as a planting medium with an automatic watering system. The method in this study was research and development using the waterfall model. In order to test the feasibility, the prototype was validated with material expert validators, media expert, and farmers. The questionnaire instrument was compiled based on Walker and Hess instrument. The results of the research found are as follows: the results of feasibility research by media experts has an average score of 4.35 with the category "very feasible", assessment by experts the material has an average score of 4.4 with the category "very feasible", and the assessment of the user has an average score of 4.06 with "feasible". The purposed controlled system of smart greenhouse and as a media for farmers was validated. Our results demonstrated that the smart greenhouse is suitable media to help farmers cultivating the tomatoes plant.